Analisis Dampak Penggunaan Media Pembelajaran Interaktif Berbasis Web Wordwall terhadap Kemampuan Divergent Thinking Matematis Siswa - Netriwati Netriwati; Mayda Ajeng Pangesti; Zahra Annisa Cahyani; Valencia Amalia Cindo; Hanun Ikrima; Carissa Aprilia (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2026)
This study aims to analyze the impact of using interactive web-based learning media Wordwall on students' mathematical divergent thinking ability. This study uses a quantitative approach with a quasi-experimental method and a pretest-posttest control group design. The study population was all grade X students of SMA Ma'arif NU 5 Purbolinggo in the 2025/2026 academic year with a sample of two classes selected using purposive sampling technique, namely the experimental class using Wordwall and the control class using conventional learning. The instrument used was a mathematical divergent thinking ability test based on four indicators according to Guilford, namely fluency, flexibility, originality, and elaboration. Data analysis used independent samples t-test and N-Gain tests. The results showed that the average post-test score of the experimental class was 77.80, higher than the control class at 68.20. The increase in student abilities in the experimental class had an N-Gain value of 0.46 with a medium category, while the control class was 0.23 with a low category. The results of the independent samples t-test showed a t-value of 4.47 and a significance value of <0.05, indicating a significant difference between the two groups. Thus, the use of web-based Wordwall learning media was proven to be more effective than conventional learning in improving students' mathematical divergent thinking skills.